Characteristics of Electricity Competency Test at Vocational High School - Made Mandalika, I.; ., Sukardi; Dahar Minghat, Asnul (International Journal of Engineering and Technology, 2018)
One of the requirements to be able to enter the business world and industry in the electricity sector is the existence of an electricity competence certificate. The electricity competency certificate is obtained after passing the electricity competency test. The electricity competency certificate is given by the Vocational High School in recognition of students who are declared competent to conduct electricity work through the electricity competency test process conducted by creditable education units and professional certification bodies. Expert competence test or often referred to as UKK is one part of the National Examination that aims to; (1) measure the achievement of students' competencies in accordance with the competencies taken; (2) facilitate students who will complete their education for graduation from education units; (3) optimizing the implementation of competency certification oriented to the achievement of vocational graduation in accordance with the Indonesian National Qualification Framework; (4) and facilitate business and industry cooperation so that the competence of graduates is in accordance with what is needed by the business world or the industrial world. The results of the competency test become indicators of the graduate competency standards contained in the Minister of National Education Regulation No. 28 of 2009, while for stakeholders will be used as information on the competencies of the workforce or vocational high school graduates. This study has following objective; (1) describe competencies in competency testing, (2) describe criteria for competency skills testing programs that are more effective, efficient, so that graduates in the Vocational High School receive full recognition from the business and industrial world.Â Â